Cavum septi pellucidi and cavum vergae cyst in man - Sasmita, Poppy Kristina; Djuartina, Tena (Atma Jaya Catholic University of Indonesia, 2011)
Introduction: The cavum septi pellucidi (CSP) and cavum vergae (CV) are cystic anomalies of septum pellucidum. Case: A 30-year-old man, which revealed cavities at the anatomical location of the CSP and CV on brain magnetic resonance imaging (MRI) because of recurrent headache. Conclusions: The CSP and CV occur during the developmental process of the brain which regresses between the seventh month of intrauterine life and the second year of postnatal life. Persistence of these structures does not cause any symptoms, but sometimes related to malformations and psychiatric disturbances, mainly dependent on size. In this case, developmental disturbance is the underlying cause.